Diuretic use before and after transcatheter aortic valve implantation: a nationwide study. (3rd October 2022) - Begun, X; Butt, J H; Kristensen, S L; Weeke, P E; Backer, O D; Schou, M; Kober, L; Fosboel, E L
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is the new standard of care in patients of older age with symptomatic severe aortic stenosis, and these patients often depend upon diuretics for symptom relief. Randomized clinical trials suggest that approximately one third of patients undergoing TAVI do not achieve symptom relief. Furthermore, some patients have more symptoms after intervention, but "real-life" data are lacking. Purpose: We examined use of diuretic therapy before and one year after TAVI in order to identify the proportion of patients who had intensification of diuretic treatment after intervention as a proxy for more symptoms. We also examined baseline factors associated with an intensification event. Methods: Using Danish nationwide registries, we identified all Danish citizens who underwent TAVI from January 1, 2008 to December 31, 2019 and were alive one year after the intervention. Diuretic use pre-TAVI and 1-year post-TAVI (based on prescription fillings) was divided into the following groups: 1) no use; 2) low diuretic use: 1–40 mg of furosemide (or equivalent bumetanide); 3) intermediate diuretic use: 41–120 mg of furosemide; and 4) high diuretic use: >120 mg furosemide. Diuretic intensification was defined as a change from one pre-TAVI diuretic group to a higher post-TAVI diuretic group. Factors associated with intensified diuretic treatment was examined with logistic regression. In this analysis of intensification, only patients who could potentially have an intensification event were included (i.e., no diuretic use, low diuretic use, or intermediate diuretic use groups). Results: A total of 3, 978 patients (median age 81 [interquartile range 77–85]; 54% men) undergoing TAVI were identified. Pre-TAVI, 1, 279 (32%) had no diuretic use, 1, 818 (46%) had low diuretic use and 881 (22%) had intermediate diuretic use. Overall, patients with pre-TAVI intermediate diuretic use had a greater burden of cardiovascular and non-cardiovascular comorbidities (higher prevalence of heart failure, atrial fibrillation, chronic kidney disease and diabetes) compared with those with no or low diuretic use. The distribution of age and sex was similar between diuretic groups. One year post-TAVI, 1, 406 (35.3%) had no diuretic use, 1, 635 (41.1%) had low diuretic use, 654 (16.4%) had intermediate diuretic use and 283 (7.1%) had high diuretic use (Figure 1). Overall, 1, 077 (27%) patients had intensification of diuretic treatment one year after undergoing TAVI. Ischemic heart disease and chronic renal failure were associated with an intensification event (odds ratio 1.23 [95% CI 1.05–1.23] and 1.46 [95% CI 1.10–1.94], respectively). Conclusion: Among patients undergoing TAVI not treated with high-dose diuretics at time of intervention, approximately 1 out of 4 patients had intensification of diuretic treatment one year after intervention. Ischemic heart disease and chronic renal failure were associated with intensification. Funding Acknowledgement: Type of funding sources: None.